Trudności w wykonywaniu pracy na stanowisku pielęgniarki pediatrycznej = Difficulties in performing work at the workplace of a paediatric nurse - Kinga Dorota Kulczycka; Monika Grenda; Ewa Stychno (Kazimierz Wielki University, 2016)
Kulczycka Kinga, Grenda Monika, Stychno Ewa. Trudności w wykonywaniu pracy na stanowisku pielęgniarki pediatrycznej = Difficulties in performing work at the workplace of a paediatric nurse. Journal of Education, Health and Sport. 2016;6(10):90-108. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.160474 http://ojs.ukw.edu.pl/index.php/johs/article/view/3926         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 12.10.2016.       Trudności w wykonywaniu pracy na stanowisku pielęgniarki pediatrycznej Difficulties in performing work at the workplace of a paediatric nurse Kinga Kulczycka1, Monika Grenda2, Ewa Stychno1   Katedra i Zakład Zarządzania w Pielęgniarstwie Wydział Nauk o Zdrowiu Uniwersytet Medyczny w Lublinie Katedra Pielęgniarstwa Collegium Mazovia Innowacyjna Szkoła Wyższa Siedlce   Chair and Department of Management in Nursing Faculty Health Sciences Medical University of Lublin Department of Nursing Collegium Mazovia Innovative School Siedlce     dr n.med. Kinga Kulczycka, mgr Monika Grenda, dr n.med. Ewa Stychno     Słowa kluczowe: obciążenie pracą, narażenie zawodowe, pielęgniarki Key words: work load, occupational exposure, nurses Streszczenie Badaniem relacji zachodzących między pracownikiem, stanowiskiem i środowiskiem pracy zajmuje się ergonomia. Nauka ta zainteresowana jest głównie poszukiwaniem jak najlepszych rozwiązań pozwalających na optymalizację procesu pracy oraz dostosowanie ich do właściwości biologicznych człowieka. Zagrożenia zdrowia w pracy pielęgniarki pediatrycznej stanowią poważny problem, zarówno medyczny jak i społeczny. Czynniki stanowiące trudności w wykonywaniu pracy zawodowej prowadzą często do nadmiernego obciążenia. Celem pracy jest wskazanie czynników wywołujących obciążenie fizyczne u pielęgniarek pracujących na oddziałach pediatrycznych. Materiał i metody : Badania przeprowadzono w grupie 110 pielęgniarek zatrudnionych na trzech oddziałach pediatrycznych od lutego do kwietnia 2015 roku. Narzędziem badawczym był  zmodyfikowany kwestionariusz do badania obciążenia  IMDS oraz ilościowy pomiar obciążenia QWI. Opracowanie STATISTICA PL 10, i EXCELL. P<=0,05. Część badawcza. Przyjmowane niefizjologiczne pozycje oraz czynności wykonywane w skręcie, pozycji kucznej i z obciążeniem kończyn górnych stanowią podstawowe trudności. Pielęgniarki postrzegają zbyt małą przestrzeń pracy, oraz skrępowanie ciała podczas realizacji zadań nad pacjentami. Wnioski:  Planowanie zadań ich przydzielanie powinno uwzględniać odpowiednie tempo i obciążenie pracą oraz indywidualne możliwości pielęgniarek umożliwiając im właściwe wykonanie obowiązków służbowych. Należy kształtować odpowiednie środowisko pracy jak i zwiększać świadomość pracowników dotyczącą czynników powodujących nadmierne obciążenie pracą fizyczną w celu ochrony ich zdrowia i zwiększania efektywności wykonywanej pracy.      Abstract Ergonomics deals with the study of relationships between an employee, workplace, and the occupational environment. This science is interested mainly in seeking the best solutions possible which allow the optimization of the work process, and the adjustment of these solutions to the biological properties of man. Health risk at the workplace of a paediatric nurse is a serious problem, both medical and social. The factors which create difficulty while performing occupational activity often lead to an excessive load. The objective of the study is the indication of factors causing physical load in nurses employed in paediatric wards. Material and methods: The study was conducted in a group of 110 nurses employed in there paediatric wards during the period from February - April 2015. The research instrument was a modified questionnaire for the examination of the IMDS load and the quantitative measurement of the QWI load. Analysis was performed using STATISTICA PL 10, and EXCELL; P<=0.05. Research part. Non-physiological positions assumed at work, and activities performed twisting, in a crouching position, and with loading the upper extremities are the primary difficulties. Nurses perceive their workspace as too small, and body restraint while performing tasks on behalf of patients.  Conclusions:  The planning of tasks and their assignment should consider a proper pace of work and work load, as well as individual capabilities of nurses, enabling them the proper performance of duty services. It is necessary to shape an adequate work environment and increase the awareness of employees concerning the factors which cause an excessive physical work load in order to protect their health, and increase the effectiveness of the work performed.